1964
DOI: 10.1111/j.1751-1097.1964.tb08777.x
|View full text |Cite
|
Sign up to set email alerts
|

Triplet State Studies of Flavins by Electron Paramagnetic Resonance—i

Abstract: Riboflavin and FAD (flavin-adenine-diucleotide) were obtained from Cal. Biochem. Co., Los Angeles, California. FMN (flavin-mono-nucleotide) was donated by Eisai Pharmacy Co., Tokyo, Japan. The estimated purity of these compounds was better than 95 per cent. D-amino acid oxidase was prepared by the method of Kubo et a/.@) and further purified with calcium phosphate gel and Sephadex G-100. MATERIALS A N D METHOD ApparatusThe EPR spectrometer used was a Varian V-4502 with associated 9-in. magnet power supply. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The semiquinone is removed by a second order reaction to form the leuco compound (FH,). In the presence of oxygen, FH, is rapidly oxidised to F' (reaction (8)) which may be identical with the starting material or may have undergone modification of the side chain while retaining the characteristic absorption peak at 445 nm. Addition of a quencher (Q) will cause loss of T by reaction (9); and a second molecule (N) with a suitably placed triplet level may be directly excited by energy transfer from T, or T, as shown in reaction ( 1 0).…”
Section: ~~mentioning
confidence: 99%
See 1 more Smart Citation
“…The semiquinone is removed by a second order reaction to form the leuco compound (FH,). In the presence of oxygen, FH, is rapidly oxidised to F' (reaction (8)) which may be identical with the starting material or may have undergone modification of the side chain while retaining the characteristic absorption peak at 445 nm. Addition of a quencher (Q) will cause loss of T by reaction (9); and a second molecule (N) with a suitably placed triplet level may be directly excited by energy transfer from T, or T, as shown in reaction ( 1 0).…”
Section: ~~mentioning
confidence: 99%
“…Tegner and Holmstrom [7], studying lumiflavin by flash-photolysis, have observed a transient absorption maximum at 650 nm, which they assign to the triplet state. Posthuma and Berends [ 11 reported phosphorescence centred at 6 10 nm from a frozen solution of riboflavin; and Shiga and Piette [8] observed EPR signals from light-excited riboflavin in a frozen matrix and ascribed these to the triplet state. Lhoste et a1.…”
Section: Introductionmentioning
confidence: 99%
“…The overall widths of the EPR spectra, the spectral positions of extreme and inflection points, and the electron‐spin polarization patterns are characteristic for photoexcited flavin triplet states generated by intersystem crossing (ISC) from excited singlet‐state precursors (57). The narrow emissive signals at 168.5 mT are the so‐called half‐field resonances arising from formal “Δ M S = ±2” transitions (58). In principle, an EPR experiment with sufficiently high time resolution reveals the full electron‐spin polarization of all transitions between the non‐Boltzmann populated (hence, electron‐spin polarized) energy levels.…”
mentioning
confidence: 99%
“…Holmstrom and Oster('*) also found that a long-lived state was the photochemically active one for riboflavin. Tether and Turnbull (16), who studied the flavinsensitized dehydrogenation of ergosterol, suggested that the triplet state of riboflavin participates in this reaction. The triplet state of flavins has been observed by electron paramagnetic resonance.…”
Section: Discussionmentioning
confidence: 99%